Nursing Care of Patients with Gastrointestinal Problems (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article explores the important role of nursing care in supporting individuals with bowel problems. From assessment and monitoring to medication administration and wound care, nurses play a critical role in providing comprehensive care and support. Understanding the importance of nursing care in the management of bowel problems can help improve the patient experience and improve their overall well-being.